Paternally multi-generational high-fat diet causes obesity and metabolic disorder through intergenerational DNA methylation - Guo, Tianyi; Hu, Zuomin; Bao, Liyuan; Cao, Yunyun; Chu, Zhongxing; Wang, Mingzhi; Li, Yan; Luo, Feijun (Frontiers in Nutrition, 2025)
ObjectivePaternal high-fat diet (HFD) has detrimental effects on offspring. However, the extent of comprehensive damage and the underlying mechanisms associated with sustained multigenerational HFD exposure remain unclear. This study aims to investigate intergenerational progressive accumulation of obesity and glycolipid metabolic disorders, as well as mechanisms mediated by DNA methylation.MethodsWe performed a novel paternally multi-generational HFD consumption model in male C57BL/6 J mice, while excluding maternal gestational effects and any confounding influences from females. The body weight and glycolipid metabolism indicators of each generation of male mice were determined. The intergenerational transmission of CpG methylation and gene expression variation was detected through mRNA microarray, methylated DNA immunoprecipitation (MeDIP)-chip, bisulfite sequencing, RT-qPCR, and Western blot etc. Analysis, to indicate genes involved in glycolipid metabolism related to the intergenerational reprogramming.ResultsThe HFD caused intergenerational accumulation of body weight increase, disturbance of glycolipid metabolism, and insulin insensitivity in male offspring. MeDIP/gene-chip results indicated that paternal HFD significantly modified gene expression and DNA methylation profiles in the liver and sperm of offspring. The majority of differential genes exhibited hypermethylation in promoter regions and reduced expression in the liver, which were linked to the glucolipid metabolic signaling pathway. The elevated promoter methylation and expression states of Spns2, Lonp1, and Hk1, which are involved in glycolipid metabolism, were inherited by offspring.ConclusionThis research shows that paternal sustained multi-generational HFD could induce intergenerational progressive accumulation of obesity and metabolic disorder through DNA methylation regulation, and identifies the target genes related to the intergenerational reprogramming, which provides new insights for the establishment of healthy diets and lifestyles.